Exploring Gender Differentials in Parents’ Perception of Children’s Television Viewing Habit in the Digital Era - Olisaeke Lovelyn Chika,; Olisaeke Festus Ife, (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
Television viewing is rapidly becoming a habit among individuals, especially children. The concerns about the effects of the habit on children informed this study. The study explores the gender differentials in parents’ perception of television viewing habit among children in the digital era. Using un/structured questionnaire, primary data were sourced from 300 parents in Pankshin, Plateau State, North-Central Nigeria. Survey design, mixed method, and content, thematic, descriptive and statistical analyses along with their allied analytical tools were employed. The results show that gender may influence parents’ perception of and attitude towards children’s television viewing habit, though the influence is insignificant. The pragmatic strategies identified for effective parental control of the habit are affirmed by majority of the respondents. The study concludes gender may influence parents’ perception of and attitude towards the habit, but it is not a determinant of their perception of and attitude towards the habit. Co-operation, collaboration, mutual understanding, and gender re/orientation are some of the recommendations made.
Keywords: Gender differentials; Parents; Perception; Children; Television viewing habit